1971
DOI: 10.2135/cropsci1971.0011183x001100040017x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Compositional Changes Resulting from Two Cycles of Directional Selection for Nutritive Value in Alfalfa1

Abstract: Progeny from three‐clone combinations of alfalfa (Medicago sativa L.) selected for high or low 6‐hour in vitro matter disappearance (6H‐DMD) had significantly different neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL) concentrations. The only significant change in cell wall composition was lower‐calculated hemicellulose (NDF‐ADF) of the cell walls of progeny from clones with high 6H‐DMD. Leaves of two‐clone combinations with high or low 6H‐DMD had similar NDF concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…These results suggest that selection for high forage quality was associated with increased leafiness of WL 252 HQ. Similar responses of increased leaf concentration following breeding for improved quality were reported by Kephart et al (1990) and Shenk and Elliott (1971) The lower leaf concentration of ORCA‐WTS may be related to its selection from European germplasm that is noted for its production of large, lodging‐resistant stems (Lamb et al, 1997) Leaf concentration was negatively correlated with total herbage yield (raverage = 0.44; P 0.05) for four of six alfalfa entries; the correlation was not significant for WL 252 HQ and ORCA‐WTS.…”
Section: Resultssupporting
confidence: 78%
“…These results suggest that selection for high forage quality was associated with increased leafiness of WL 252 HQ. Similar responses of increased leaf concentration following breeding for improved quality were reported by Kephart et al (1990) and Shenk and Elliott (1971) The lower leaf concentration of ORCA‐WTS may be related to its selection from European germplasm that is noted for its production of large, lodging‐resistant stems (Lamb et al, 1997) Leaf concentration was negatively correlated with total herbage yield (raverage = 0.44; P 0.05) for four of six alfalfa entries; the correlation was not significant for WL 252 HQ and ORCA‐WTS.…”
Section: Resultssupporting
confidence: 78%
“…Modifying cell walls can be done by recurrent selection, by marker‐assisted QTL introgression, or through transgenic approaches. Selection has been effective at modifying alfalfa for forage nutritive value (Coors et al, 1986; Demment et al, 1986; and Shenk and Elliott, 1971), essentially the same changes that are needed for bioethanol production. Genetic mapping to identify QTL affecting cell wall composition, and thereby conversion efficiency of biomass into ethanol, can be used to identify natural allelic variation that could be incorporated into breeding populations via marker‐assisted selection.…”
mentioning
confidence: 99%
“…Compared to Beaver, AC Grazeland Br has thicker epidermal and mesophyll cell walls (Goplen et al 1993), longer stems and internodes, and slightly higher concentrations of neutral detergent fiber and acid detergent fiber (Coulman, unpublished data). Similarly, Shenk and Elliott (1971) found that synthetics of alfalfa selected for low 6 h in vitro dry matter disappearance were higher in neutral detergent fiber concentration than synthetics selected for high in vitro dry matter disappearance.…”
Section: Releasementioning
confidence: 87%